IMPLEMENTASTION OF BUSINESS ETHICS IN VESPA SALES AND PURCHASE AGREEMENTS IN THE SCOOTER GARAGE KRANGKENG INDRAMAYU PERSPECTIVE SHARIA ECONOMI LAW - Yogi Prasetio (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze in depth the implementation of islamic business ethics in the sale and purchase of classic Vespa motorcycles at Garage Scooter krangkeng, Indramayu Regency, trough the perspective of Sharia Economic Law. As part of sociological phenomenon and contemporary automotive creative economy, transactions of used motorcycles with high historical value are often faced with technical information asymmetry between business actors and consumers. This study uses a qualitative-descriptive method with a normative-empirical case study approach. Primary data were collected directly from the field through participatory observation and in-depth interviews with Garage Scooter owners and consumers, while secondary data were obtaied through participatory observastion and-depth interviews with Garage Scooter owners and consumers, national regulitions. The result of the study indicate thet transaction practices at Garage Scooter Kangkeng are carried out through a direct sale and purchase scheme (bal’ musawamah) and an indent system for ordering modification restorations. Business actors have implemened basic islamic business ethics values such as honesty (shiddiq0, trustworthiness, transparancy, and reponsibility for product qualit. However, crucial loopholes are still found in the form of weak black and white doumentation (written contracts), which opens up the potential fo uncertainty (gharar) and manipulation of minor information (tadlis)related to detalled machine specifacitions and the accuracy of restoration times. Viewed form Shari Economic La, the validity of The pillar and conditions of commodity objects requires strengthening after-sales technical tansparancy through written instruments (al-kitabah) to uphold the principle of mutual consent (an-tardhin) and the right to choose (khiyar al-‘aib) in order to achieve tru benefit (maslahah).